Postural and craniocervical dysfunctions and their relationship to the voice of women with cervical pain (Research, Society and Development, 2020)
Introduction: Altered body alignment may contribute to the onset of muscle hypertension in the cervical region. Alterations in the cervical region can generate several complications, including pain and hypertension during phonation. Objective: To relate the postural with functional alterations of the craniocervical region and the voice of women complaining of musculoskeletal pain in the cervical region. Methods: Case study with ten women complaining of cervical pain. Assessments: Craniocervical Dysfunction Index, photogrammetry, maximum vowel phonation time of the vowel /a/, and sound pressure level. Results: Craniocervical Dysfunction Index: 100% dysfunction. Maximum phonation time /a/: 100% decreased. There was a moderate significant positive correlation between these variables. Photogrammetry: all participants presented alterations in the calculated alignments. Sound pressure level: 90% altered. Conclusion: There were postural and functional dysfunctions in the craniocervical region and vocal alteration, suggesting that vocal imbalances are more related to functional than postural alterations of the craniocervical region.